PENERAPAN UNSUR TINDAK PIDANA PERBUATAN CURANG DALAM PERIKATAN OLEH PENYIDIK PADA DIREKTORAT RESERSE KRIMINAL UMUM POLDA SUMBAR - Fenni Gusman (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
The investigation by the West Sumatra Regional Police's Ditreskrimum wascarried out by a contractor who purchased building materials at several shopsand did not pay any payment for the purchase of building materials, thus causingthe loss of building materials shop owners. The application of the elements of thecriminal act of fraudulent acts in the engagement by investigators at the WestSumatra Regional Police's Ditreskrimum consists of subjective and objectiveelements. Subjective elements are people who can be held accountable for theiractions. The presence of